Modeling moisture adsorption isotherms for extruded dry pet foods - da Silva, Mayara Uana; Sato, Joyce; Ribeiro, Priscila Martins [UNESP]; Janeiro, Vanderly; Ribeiro, Leonir Bueno; Vasconcellos, Ricardo Souza (Elsevier, 2022)
Two mathematical models were used to determine the moisture adsorption isotherm curves of dry pet foods. Ten extruded commercial diets for dogs (n = 6) and cats (n = 4) were tested within 7 days of manufacture. The equilibrium moisture content of each food at 30 and 40 °C was determined by gravimetry. Six saturated saline solutions (lithium chloride, potassium acetate, sodium nitrite, magnesium chloride, sodium chloride, and potassium chloride) were prepared and used to obtain pet food samples at different water activities. Solutions were placed in airtight flasks containing food samples (without direct contact) and oven-dried to constant weight. The relationship between water activity and equilibrium moisture content was modeled by the exponential Peleg and Guggenheim–Anderson–de Boer (GAB) models. All pet foods exhibited a type II isotherm. Akaike information criterion, R2, and standard deviation values were − 29.79, 0.914, and 3.89, respectively, at 30 °C by the Peleg model; − 28.86, 0.876, and 6.36 at 40 °C by the Peleg model; − 31.17, 0.937, and 4.34 at 30 °C by the GAB model; and − 29.63, 0.888, and 7.71 at 40 °C by the GAB model. At 0.60 water activity, equilibrium moisture contents by the Peleg and GAB models were 12.04 ± 0.84 and 11.67 ± 0.78 g H2O/g dry matter, respectively, at 30 °C and 7.83 ± 1.31 and 8.09 ± 0.81 g H2O/g dry matter at 40 °C. The GAB model also allowed estimating monolayer moisture content (5.81 ± 0.81%). Both models provided similar results and may be useful for determining quality parameters for pet foods. Adsorption isotherm studies can provide practical information about the moisture ranges of pet foods, contributing to the optimization of food safety, palatability, and processing conditions.
Keywords: Equilibrium moisture; Food safety; Monolayer water; Shelf-life; Water activity